Present Status and Future Prospects of Tropical Mushroom Cultivation in India: A Review - THAKUR, M.P. (Indian Phytopathology, 2014)
Mushrooms are biota characterized by wonder. These are the fruiting bodies of macrofungi which are devoid of leaves and of chlorophyll-containing tissues. Yet, they grow and produce new biomass. Mushroom mycelia secrete enzymes that break down compounds such as cellulose and lignin which are then absorbed by the hyphae. Mushrooms are very nutritious products. It can serve as food, tonic, and as medicine. They are rich in crude fibre, proteins and vitamins but low in fat and calories. They possess multi-functional medicinal properties. Mushroom cultivation has great scope in India and in some of other developing countries because of the cheap and easy availability of raw materials. Mushroom cultivation technology is ecofriendly and is a labour intensive activity. Therefore, it will serve as means of generating employment, particularly for rural women and youths in order to raise their social status. It will also provide additional work for the farmers during winter months when the farming schedule is light. The production of tropical mushrooms like oyster (Pleurotus spp.), paddy straw (Volvariella volvacea) and milky mushroom (Calocybe indica) utilizing locally available agricultural wastes viz., paddy straw, wheat, soybean, chickpea, mustard, lathyrus, cotton wastes and lignocellulosic wastes are exploited. The production of oyster mushroom in India is estimated to be around 15-20,000 metric tonnes. However, the production of paddy straw and milky mushroom is about 10,000 tonnes each. Oyster mushroom farming is largely done by the women of the self help groups in a small to medium scale. It constitutes an important source of their income. Paddy straw (Volvariella volvacea) mushroom is very popularly grown in Orissa. Milky mushrooms can be cultivated throughout the year in the entire plains of India. It is hoped that the advocation of mushroom farming will become a very important cottage industry activity in the integrated rural development programme.